THE IMPLEMENTATION OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TO PROMOTE READING COMPREHENSION IN ELEMENTARY SCHOOL - Fidrayani, Fidrayani; Julia, Maya (JMIE (Journal of Madrasah Ibtidaiyah Education), 2017)
Many aspects of life need reading activities. Reading to understand the meaning of words called reading comprehension. This study is using descriptive analysis to determine how the implementation of the Cooperative Integrated Reading and Composition (CIRC) to promote reading comprehension. The aspects in reading comprehension are: a) the ability to grasp the meaning of words and phrases used by the author, b) the ability to grasp the meaning of explicit and implicit meaning, c) the ability to make inferences. Steps in the CIRC are: a) forming a group with four to five students are heterogeneous, b) the teacher gives an explaining in accompliance with the learning topics, c) students work together,Â  reading and find the main idea and give a response to the discourse and written on a sheet of paper, d) presented the results of the group, e) the teacher makes a conclusion with his students, f) ending the class. Implementation CIRC in reading comprehension are already visible in measures of activities so that learning objectives can be achieved and reading comprehension can also be developed. Implementation CIRC in reading comprehension can be used by further research using distinct methodologies.